Humanistic elements in the educational practice at a United States sub-baccalaureate technical college - Peng Chen; Carsten Schmidtke (International Journal for Research in Vocational Education and Training (IJRVET), 2017)
Humanism has never been able to establish a firm place in technical education, which remains predominantly pragmatist in response to industry needs, certification requirements and educational standardisation. However, after a period of decline, humanism has made somewhat of a comeback as part of the movement toward student-centred education. Research conducted at a technical college showed that although humanistic elements are largely absent from educational practice in post-secondary technical education, they are not detrimental to the achievement of stated educational objectives. This research indicated that including humanistic elements in educational practice will enable instructors to be more effective in helping students to develop skills in relation to team work, problem-solving, systems improvement, lifelong learning and other areas that are becoming increasingly necessary for success in the workplace. The specific recommendations from this research include a constructivist approach with a focus on contextual teaching and learning using situated cognition, cognitive apprenticeships, anchored instruction and authentic assessment. At the same time, some suggestions for improving professional development for teachers by using a Gestalt approach along with self-study in the context of learning communities have been discussed.
Keywords: 330; VET; Vocational Education and Training; Technical Education; Vocational Education; Humanism; Humanistic Methods; Educational Practice